2016
DOI: 10.1371/journal.pone.0158299
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Vascular Cell Adhesion Molecule-1 (VCAM-1) as a Biomarker in the Mouse Model of Experimental Autoimmune Myocarditis (EAM)

Abstract: Vascular cell adhesion molecule-1 (VCAM-1) is strongly upregulated in hearts of mice with coxsackie virus-induced as well as in patients with viral infection-triggered dilated cardiomyopathy. Nevertheless, the role of its soluble form as a biomarker in inflammatory heart diseases remains unclear. Therefore, we investigated whether plasma levels of soluble VCAM-1 (sVCAM-1) directly correlated with disease activity and progression of cardiac dysfunction in the mouse model of experimental autoimmune myocarditis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…Consistent with previous studies [ 27 , 45 ], Lp(a) upregulates the expression of adhesion molecules, especially VCAM-1, ICAM-1, and E-selectin, in the inflammatory status, such as AMI. Furthermore, our cell-based ELISA demonstrated that garcinol reduced the Lp(a)/α7-nAChR-induced expression of VCAM-1, ICAM-1, and E-selectin and proinflammatory cytokines (IL-6, TNF-a, CRP, and NF-κB).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies [ 27 , 45 ], Lp(a) upregulates the expression of adhesion molecules, especially VCAM-1, ICAM-1, and E-selectin, in the inflammatory status, such as AMI. Furthermore, our cell-based ELISA demonstrated that garcinol reduced the Lp(a)/α7-nAChR-induced expression of VCAM-1, ICAM-1, and E-selectin and proinflammatory cytokines (IL-6, TNF-a, CRP, and NF-κB).…”
Section: Discussionsupporting
confidence: 91%
“…ICAM-1 and VCAM-1 in aorta may have an important role in the initiation of atherogenesis, while in cardiac tissue, ICAM-1 and VCAM-1 are reported to be upregulated in several studies at the onset of pressure overload by aortic constriction and in the presence of cardiac inflammation such as in myocardial infarction or inflammatory cardiomyopathy [12-15]. Soluble VCAM-1 also is an established biomarker to predict future or long-term acute coronary syndrome [23-25].…”
Section: Resultsmentioning
confidence: 99%
“…ICAM-1 has been known to be upregulated at the onset of pressure overload by aortic constriction and in the presence of cardiac inflammation mediates T-cell recruitment during pathologic cardiac remodelling in heart failure [12-14]. VCAM-1 is strongly upregulated in the heart during acute and chronic stages of diseases such as in inflammatory cardiomyopathy [15]. This study was aimed to explore ICAM-1 and VCAM-1 expression of cardiac tissue from the early progression of atherosclerosis in dyslipidemia in Sprague Dawley rat model.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the mediation role of CAMs in ventricular pacing associated with myocardial inflammatory responses has been uncovered [ 28 ]. Of note, vascular CAM-1 has been shown to be a biomarker of experimental autoimmune myocarditis [ 29 ]. These studies support our results.…”
Section: Discussionmentioning
confidence: 99%